RABIES PERTAMA DI BALI - Susilawathi NM*, Satriawan *, Laksmidewi**, Raka Sudewi AA** (NEURONA, 2009)
IS ZOONOSIS OF CERTAIN MAMMAL SPECIES ENDEMIC IN ALL CONTINENTS DOGS ARE THE MAJOR RESERVOIRS AND PLAY PIVOTAL ROLE IN RABIES TRANSMISSION RABIES IS AN ACUTE VIRAL ENCEPHALOMYELITIS WHICH IS VIRTUALLY FATAL BALI NUSA TENGGARA BARAT AND PAPUA ARE DECLARED HISTORICALLY FREE OF RABIES HERE WE REPORT THE FIRST RABIES IN BALI KEYWORDS RABIES FIRST CASE BALI